Isolation, Cellulase Activity Test and Molecular Identification of Selected Cellulolytic Bacteria Indigenous Rice Bran - Akyunul Jannah; Aulanni`am Aulanni`am; Tri Ardyati; Suharjono Suharjono (Universitas Gadjah Mada, 2018)
Rice bran is the waste product of rice milling which is abundant in Indonesia, it can be used as a raw material for the manufacture of bioethanol by fermentation. Before being fermented, rice bran must be hydrolyzed into glucose by biomass degrading. This study was aimed to isolate indigenous cellulolytic bacteria from rice bran as producer of cellulolytic enzymes and resulted in 22 bacterial isolates that demonstrated cellulolytic activity being identified. Among them, BE 8 and BE 14 isolates showed the highest endoglucanase activity at 2.16 and 1.31 U/mL respectively. Identification of the 16S rDNA showed that BE 8 belongs to Bacillus subtilis and BE 14 in Bacillus cereus.